The effect of employee engagement and training on employee performance through organizational commitment - Elisabeth Sibarani; Isfenti Sadalia; Nazaruddin Nazaruddin (Institute of Computer Science (IOCS), 2023)
The existence of organizational change results in a decrease in the quality of employee performance which must be supported by training so that it can respond to market changes and competition. The purpose of this study was to analyze the effect of employee engagement and training on employee performance through organizational commitment. The sample in this study amounted to 89 respondents. The statistical method used is inferential statistics (inductive statistics or probability statistics) with PLS (Partial Least Square) to complete the hypothesis. The results of this study are that there is a positive and significant influence of employee engagement, training, and organizational commitment on employee performance through organizational commitment. This research has implications for the managerial part of the company where training is needed, especially those related to benefits in completing work.